Pembiasaan Harian Siswa Berbasis Komunikasi Profetik: Studi Kasus di SD Islam Terpadu Idrisiyyah - Hasan, In’amul (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2020)
This research aims to analyze the daily habits of students at Idrisiyyah Integrated Islamic Elementary School which is based on prophetic communication. Prophetic communication refers to a way of interacting that not only prioritizes academic aspects, but also moral and spiritual values. The problem in this research is how the daily habits of Idrisiyyah Integrated Islamic Elementary School students are based on Prophetic Communication. The aim of this research is to find out how the daily habits of Idrisiyyah Integrated Islamic Elementary School students are based on prophetic communication. The method used is through a qualitative approach, this research collects data from observation, interviews and documentation. The research results show that the application of prophetic communication in students' daily habits, which consists of the values ​​of liberation, humanization and transcendence, is able to improve students' academic and moral performance. Apart from that, prophetic communication also contributes to strengthening students' character which is in line with the school's vision and mission. This approach has succeeded in increasing students' spiritual awareness, strengthening their relationship with Allah, and forming a strong Islamic character in everyday life. Keywords: Habituation, Communication, Prophetic